Tactile 3D microprobe system with exchangeable styli - Balzer, Felix; Hausotte, Tino; Vorbringer-Dorozhovets, Nataliya; Manske, Eberhard; Jäger, Gerd (Measurement Science & Technology, 2011)
Over the past decade a trend of component miniaturization can be observed both in industry and in the laboratory, which involves an increasing demand for nanopositioning and nanomeasuring machines as well as for miniature tactile probes for measuring complex three-dimensional objects. The challenge is that these components-for example, diesel injectors, microgears and small optics-feature dimensions in the micrometre range with associated dimensional tolerances below 100 nm. For this reason, a significant number of research projects have dealt with microprobes for performing the dimensional measurements of microstructures with the goal of achieving measurement uncertainties in the nanometre range. This paper introduces an updated version of a 3D microprobe with an optical detection system developed at the Institute of Process Measurement and Sensor Technology. It consists of a measuring head and a separate probe system. The mechanical design of the probe system has been completely overhauled to enable the exchange of the stylus separately from the flexure elements. This is very important for the determination of the probing sphere's roundness deviations. The silicon membranes used in the first system design are therefore replaced by metal membranes. A new design of these membranes, optimized for isotropic probing forces and locking parasitic movements, is presented. Regarding the measuring head, the optical design has been redesigned to eliminate disruptive interference on the quadrant photodiode used for deflection measurement and to improve adjustment. Its dimensioning is discussed, especially the influence of the laser beam diameter on the interference contrast due to the parallel misalignment of the collimated laser beam. Initial measurement results are presented to prove functionality.
Keywords: micrometrology; microprobe; optical detection; exchangeable styli